THE EFFECT OF BONUS PACKS AND PRODUCT QUALITY ON PURCHASE DECISIONS AT PT. ALAMJAYA WIRASENTOSA TG. MORAWA DELI SERDANG NORTH SUMATRA - Husna Ulfah (PT. Jurnal Center Indonesia Publisher, 2026)
ABSTRACT The purpose of this study was to determine the effect of bonus packs and product quality on consumer purchasing decisions at PT. Alamjaya Wirasentosa Tg. Morawa Deli Serdang, North Sumatra. The population in this study are consumers at PT. Alamjaya Wirasentosa Tg. Morawa Deli Serdang North Sumatra as many as 379 consumers for one week while the determination technique is random sampling with the withdrawal technique using the Slovin formula. So that the sample in this study amounted to 79 respondents. The sources of data in this study are primary data and secondary data. Where the primary data from observations, interviews and questionnaires. While secondary data can be from data that has been documented. While the data analysis techniques used are descriptive analysis and multiple linear regression. The results of multiple regression analysis are Y = 8.898 + 0.193X1 + 0.548X2 + e which shows that the bonus pack and product quality have a positive and significant effect on consumer purchasing decisions. While the results of the (t) test or partial test show that the bonus pack has a positive and significant effect on consumer purchasing decisions where it can be seen that the tcount value is 2.125 > ttable 1.992 and the product quality variable also has a positive and significant effect on consumer purchasing decisions where it can be seen that the tcount value is 9.425 > ttable 1992. The results of the coefficient of determination with a correlation regression value of 0.814, meaning that together the bonus pack and product quality on consumer purchasing decisions at PT. Alamjaya Wirasentosa Tg. Morawa Deli Serdang North Sumatra has contributed to a strong degree. Then the coefficient of determination (R2) is 0.653 (65.3%). So it can be said that 65.3% of the variation in the dependent variable, namely the bonus pack and product quality in the model, can explain the purchasing decision variables at PT. Alamjaya Wirasentosa while the remaining 34.7% is influenced by other variables outside the model. Keyword: Bonus Pack, Product Quality, Purchase Decision